Improving Employee Performance Through Competence, Communication, and Work Environment with Motivation as Mediation - Nugroho, Bambang Haryo; Tubastuvi, Naelati; Purwidianti, Wida; Darmawan, Akhmad (Universitas Muhammadiyah Sorong, 2025)
This study uses work motivation as a mediator to look at how competence, communication, and the work environment affect employee performance. This study takes a quantitative method, distributing questionnaires with a Likert scale assessment as the primary means of gathering data. The study's population, which is made up of 609 workers from Islamic banks in Indonesia who work as relationship managers and customer service representatives, has a sample size of 254 respondents, which was calculated using the Slovin formula. Software called Smart PLS (Partial Least Square) was used to analyze the data. The conclusion that work atmosphere, competency, and communication all favorably affect motivation. Additional findings demonstrate that motivation, work environment, competency, and communication all favorably impact employee performance. Furthermore, the relationship between competence and employee performance cannot be mediated by motivation, but it can be mediated by the relationship between communication and the work environment on employee performance.